Expressive Speech Acts found in Orion and the Dark Movie - Maharani, Putri Dhea Sahara; Handayani, Nurma Dhona (Humanitatis : Journal of Language and Literature, 2024)
Expressive speech acts are designed by the speaker so that the utterance is interpreted as an evaluation of the thing mentioned in the utterance. Expressive speech can be praising, thanking, congratulating, criticizing, insinuating, complaining, and blaming. This research aims to interpret expressive speech acts, describe the types of expressive speech acts, and analyze the form of expressive speech acts in Orion and the Dark Movie. The qualitative method was used because this study aimed to determine the types of speech acts, especially expressive ones, found in Orion and the Dark Movie (2024). The researchers analyzed the data using the pragmatic identity method. The analysis found that 21 expressive speech acts were used in the movie. The most frequently used expressive speech acts are complaining 6 times, apologizing 1 time, congratulating 1 time, thanking 5 times, protesting 1 time, greeting 1 time, welcoming 1 time, and complimenting 7 times. The absent ones are the condole, boast, and deplore.